2010
DOI: 10.4317/medoral.15.e483
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of platelet-rich plasma, hydroxyapatite, demineralized bone matrix and autologous bone to promote bone regeneration after mandibular impacted third molar extraction.

Abstract: A comparative study of platelet-rich plasma, hydroxyapatite, demineralized bone matrix and autologous bone to promote bone regeneration after mandibular impacted third molar extraction AbstractObjectives: 1) to compare mandibular bone regeneration by applying autologous bone, platelet-rich plasma and two biomaterials (synthetic calcium hydroxyapatite, and demineralized bone matrix), and thus establish the potential benefits of these biomaterials in the regeneration of postextraction alveolar bone, 2) to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…The Authors observed no further acceleration in bone formation at 6 months nor did they observe statistically significant differences between the groups regarding pain, swelling, trismus and infection throughout the post-operative period. [38]. Similarly, in a study by Gurbuzer et al .…”
Section: Methodsmentioning
confidence: 77%
“…The Authors observed no further acceleration in bone formation at 6 months nor did they observe statistically significant differences between the groups regarding pain, swelling, trismus and infection throughout the post-operative period. [38]. Similarly, in a study by Gurbuzer et al .…”
Section: Methodsmentioning
confidence: 77%
“…Therefore, high centrifugal forces applied to dolphin whole blood may compromise the integrity of platelets and render them inadequate for high quality PRP isolation due to loss of platelet integrity. This error in the technical step of PRP preparation and isolation may help to explain some reports indicating non-beneficial effects of PRP treatment [36]. Furthermore, our initial studies utilizing fewer revolutions (<900 rpm) were unable to concentrate the platelets to levels different than that of whole blood, i.e., lower centrifugal forces did not produce PRP in dolphin blood samples.…”
Section: Discussionmentioning
confidence: 89%
“…The lesion area and an adjacent bone area in each radiograph were also cropped by means of the Adobe Photoshop program. The ratio between the radiographic density of the lesion area and the adjacent bone area was obtained in each group [18].…”
Section: Radiographical Assessmentmentioning
confidence: 99%
“…On the contrary, Sanchez et al [17] have pointed out the lack of evidence on the efficacy of PRP in combination with bone grafts during augmentation procedures in a review. In another study by Arenaz-Bua et al [18], acceleration in bone formation has not been observed when PRP is placed in third molar extraction sites and it was concluded that PRP ease manipulation and acts as a perfect carrier when used in combination with other graft materials. In a Cochrane systematic review of randomized controlled clinical trials no reliable evidence has been found on promotion of bone healing with platelet-rich plasma, in conjunction with implant treatment [19].…”
Section: Introductionmentioning
confidence: 96%